(untitled) (Religious dialogue and cooperation, 2023)
Religious actors are often called to take an active part in initiatives promoted by European Institutions because of their potential to prevent conflict and ease social tensions that can arise among people of different religions. Member States are called to support a sustained, open and transparent dialogue with the different religions communities as a tool for peacekeeping and promoting social cohesion in Europe and at its borders. The role of local authorities is crucial in this process; virtuous cases are the Italian municipalities of Novellara and Reggio Emilia, whose abilities to value the presence of Sikh and Hindu communities in their territories led to the publication of a Handbook for Local Authorities, titled “Valuing religious communities as key actors of social cohesion”, with the patronage of the Council of Europe: an example of how local best practices can influence European principles from the bottom up. The paper aims to explore in detail the different ways in which these religious actors and local governments collaborate and cooperate: the enhancement of places of worship, the promotion of interfaith dialogue and the shared participation in religious festivities. These are policy strategies aimed towards a collective education for plural and inclusive citizenship.